The Textual Life of Dickens's Characters - Davies, James A. author. aut Link
VIII, 187 p.
Keywords: By focusing on selected characters and characterizations from all stages of Dickens' literary career, both fiction and non-fiction, this book looks at the thematic significance of the modern distinction between story and text.